The First Draft of the First World History: Rashīd al-Dīn’s Initial Proposal for Jāmiʿ al-tawārīkh - Kamola, Stefan T. (JAOS, 2025)
Rashīd al-Dīn Ṭabīb (d. 1318) has been called the "first world historian" because of how foreign historical sources are treated in the second volume of his Jāmiʿ al-tawārīkh. New manuscript materials have shown, however, that his contemporary courtier and historian, ʿAbd Allāh Qāshānī, is likely the real author of much of the Jāmiʿ. This article advances the discussion about the creation of Jāmiʿ al-tawārīkh by describing and analyzing an alternate version of Rashīd al-Dīn’s introduction to the collection. This alternate introduction, preserved in a single manuscript in Munich, suggests that Rashīd al-Dīn initially had a very different purpose in mind for his world history than what has come down to us, envisioning it not as an ecumenical description of the world but as a programmatic argument for his patrons’ sovereign legitimacy. Examining this alternate introduction forces us to rethink Rashīd al-Dīn’s historiographical motive. It also helps answer open questions about the structure of Jāmiʿ al-tawārīkh, its production, and how Qāshānī’s text came to be included in it.